18FDG-PET-CT improves specificity of preoperative lymph-node staging in patients with intestinal but not diffuse-type esophagogastric adenocarcinoma. Issue 1 (January 2017) - Lehmann, K.; Eshmuminov, D.; Bauerfeind, P.; Gubler, C.; Veit-Haibach, P.; Weber, A.; Abdul-Rahman, H.; Fischer, M.; Reiner, C.; Schneider, P.M.
Abstract: Introduction: The accuracy of preoperative lymph-node staging in patients with adenocarcinoma of the esophagogastric junction (AEG) or gastric cancer (GC) is low. The aim of this study was to assess the accuracy of [18F]fluorodeoxyglucose positron emission tomography/computed tomography (PET-CT) for lymph-node staging in patients with AEG or GC, with or without neoadjuvant treatment. Patients and methods: 221 consecutive patients with GC (n = 88) or AEG (n = 133) were evaluated. Initial staging included endoscopic ultrasound (EUS), multidetector spiral CT (MDCT) and PET-CT. PET-CT was performed for restaging in patients after neoadjuvant treatment (n = 94). Systematic lymphadenectomy was routinely performed with histopathological assessment of individual mediastinal and abdominal lymph-node stations. Preoperative staging from EUS, MDCT, and PET-CT was correlated with histopathological results. Results: PET-CT showed a high specificity (91%) and positive predictive value (89%) for the preoperative detection of lymph-node metastases. In comparison, EUS was more sensitive (73% versus 50%, P < 0.01) but less specific (60%, P < 0.01). In patients with intestinal/mixed-type tumors, PET-CT improved the detection of extra-regional lymph-node metastases ( P = 0.01) and distant metastases ( P = 0.01) compared to CT alone. In contrast, lymph-node assessment by PET/CT after neoadjuvant treatment (32%, P < 0.01) and in diffuse-type cancers (24%, P < 0.01) is futile because of low sensitivities. Conclusion: PET-CT does not improve the overall accuracy of N staging, but does improve specificity compared to EUS and MDCT in AEG and GC. We do not recommend routine PET-CT for the initial staging in patients with diffuse-type cancer or for restaging of lymph nodes after neoadjuvant treatment.